2011
DOI: 10.1093/nar/gkr1139
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Musashi1 in a complex with target RNA: the role of aromatic stacking interactions

Abstract: Mammalian Musashi1 (Msi1) is an RNA-binding protein that regulates the translation of target mRNAs, and participates in the maintenance of cell ‘stemness’ and tumorigenesis. Msi1 reportedly binds to the 3′-untranslated region of mRNA of Numb, which encodes Notch inhibitor, and impedes initiation of its translation by competing with eIF4G for PABP binding, resulting in triggering of Notch signaling. Here, the mechanism by which Msi1 recognizes the target RNA sequence using its Ribonucleoprotein (RNP)-type RNA-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
142
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(153 citation statements)
references
References 61 publications
11
142
0
Order By: Relevance
“…The UAG trinucleotide, which has been previously reported as the core of the MSI1 binding site (43), was generally enriched around MSI1 iCLIP sites ( Fig. 1B and C).…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…The UAG trinucleotide, which has been previously reported as the core of the MSI1 binding site (43), was generally enriched around MSI1 iCLIP sites ( Fig. 1B and C).…”
Section: Resultssupporting
confidence: 62%
“…Nuclear magnetic resonance structures have suggested that the two RNA recognition motif (RRM) domains of MSI1 act independently to recognize RNA motifs (43). We investigated the tendency of UAG/GUAG motif pairs, in contrast to isolated UAG or GUAG sequences, to occur at iCLIP sites compared to flanking regions in different contexts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we applied NMR methods to Msi1 RBD1 and RBD2 individually, and determined the solution structures in their free forms, identified the residues involved in RNA-binding, and assessed the backbone dynamics and discussed the origin of high RNA-binding affinity [8,9]. Our subsequent NMR analysis identified the minimal recognition RNA sequences for Msi1 RBD1 and RBD2 to be r(GUAG) and r(UAG), respectively [10]. Then, we determined the NMR solution structure of Msi1 RBD1-r(GUAGU) complex, which clearly revealed the detailed interactions between Msi1 RBD1 and r(GUAG) [10].…”
mentioning
confidence: 99%
“…Our subsequent NMR analysis identified the minimal recognition RNA sequences for Msi1 RBD1 and RBD2 to be r(GUAG) and r(UAG), respectively [10]. Then, we determined the NMR solution structure of Msi1 RBD1-r(GUAGU) complex, which clearly revealed the detailed interactions between Msi1 RBD1 and r(GUAG) [10]. Furthermore, a theoretical analysis based on statistical mechanics of hydration was applied to Msi1 RBD1-r(GUAG) interaction to provide a deeper understanding into the recognition mechanism [11].…”
mentioning
confidence: 99%